Antitumor Activity of Auger Electron Emitter 111In Delivered by Modular Nanotransporter for Treatment of Bladder Cancer With EGFR Overexpression - Rosenkranz, Andrey A.; Slastnikova, Tatiana A.; Karmakova, Tatiana A.; Vorontsova, Maria S.; Morozova, Natalia B.; Petriev, Vasiliy M.; Abrosimov, Alexey S.; Khramtsov, Yuri V.; Lupanova, Tatiana N.; Ulasov, Alexey V.; Yakubovskaya, Raisa I.; Georgiev, Georgii P.; et al. (Frontiers in Pharmacology, 2018)
Gamma-ray emitting 111In, which is extensively used for imaging, is also a source of short-range Auger electrons (AE). While exhibiting negligible effect outside cells, these AE become highly toxic near DNA within the cell nucleus. Therefore, these radionuclides can be used as a therapeutic anticancer agent if delivered precisely into the nuclei of tumor target cells. Modular nanotransporters (MNTs) designed to provide receptor-targeted delivery of short-range therapeutic cargoes into the nuclei of target cells are perspective candidates for specific intracellular delivery of AE emitters. The objective of this study was to evaluate the in vitro and in vivo efficacy of 111In attached MNTs to kill human bladder cancer cells overexpressing epidermal growth factor receptor (EGFR). The cytotoxicity of 111In delivered by the EGFR-targeted MNT (111In-MNT) was greatly enhanced on EJ-, HT-1376-, and 5637-expressing EGFR bladder cancer cell lines compared with 111In nontargeted control. In vivo microSPECT/CT imaging and antitumor efficacy studies revealed prolonged intratumoral retention of 111In-MNT with t½ = 4.1 ± 0.5 days as well as significant dose-dependent tumor growth delay (up to 90% growth inhibition) after local infusion of 111In-MNT in EJ xenograft-bearing mice.